What do we currently know about urticaria in children? - Anna Góra; Majka Jaszczura; Małgorzata Morawiecka-Pietrzak; Magdalena Kleszyk; Edyta Machura (Termedia Publishing House, 2022)
Urticaria is a common pediatric dermatosis characterized by local swelling, pruritus, and skin redness. The primary lesions include wheals and/or angioedema. By definition, acute urticaria lasts up to 6 weeks and usually occurs as a single episode in life. Chronic urticaria lasts over 6 weeks and is uncommon. Urticaria is a heterogenous disease. The development of skin lesions depends on the action of mast cells and other cells of the immune system, and inflammation is common in all forms of urticaria. Autoimmune mechanisms and activation of coagulation and fibrinolysis also play an important role. The etiology usually remains unknown. Urticaria, especially its chronic form, contributes to a significant decrease in quality of life due to prolonged discomfort and the necessity of long-term and sometimes expensive treatment. This article presents an up-to-date review of the literature on the incidence, causes, diagnosis, treatment and prognosis of urticaria in children.